(untitled) (Sociologisk Forskning, 1997)
Violence and the city. A critical assessment of Swedish criminology Violence and urban life, particularly street violence, is currently a prominent public issue, of rising importance to various social sciences. Disciplinary, however, there is, traditionally, a double starting point here, one rooted in criminology, the other in urban sociology. Departing in a specific understanding of the urban order as a liminal space subjugated to several forms of social control, this article is aimed at a critical assessment of Swedish criminology, particularly the work of P-O Wikström. Two instances of this empiricist discourse are scrutinised. First a general model relating level of crime to level of urbanisation, the essence of which is shown to be the so called routine activity approach, is examined step by step. Second, the dimensions of violent crime in terms of place and social relations is discussed critically.